Validation of food variety and dietary diversity scores as indicators of micronutrient adequacy among pregnant women in the northern zone of Sidama, Ethiopia - Mayisso, Kaleb; Bosha, Tafese; Tamiru, Dessalegn (Frontiers in Public Health, 2025)
BackgroundA diet that includes a variety of foods provides all the essential nutrients needed to meet nutritional requirements. However, the relationship between dietary diversity and adequate micronutrient intake has not been consistently established across various cultural contexts. Notably, no studies have successfully validated a link between dietary diversity scores and nutrient adequacy in Ethiopia. Therefore, we aimed to validate food variety and dietary diversity scores as proxy indicators of nutrient adequacy among pregnant women in Ethiopia.Materials and methodsA multi-stage systematic random sampling method was used to select study participants from March 1 to March 30, 2024. The multiple-pass 24-h dietary recall method, incorporating the standard nine food groups, was employed to estimate the dietary diversity score of pregnant women. The nutrient adequacy ratio (NAR) was calculated based on the mean adequacy ratio of various micronutrients. Receiver operating characteristic (ROC) curve analysis was used to determine optimal cutoffs for dietary diversity and food variety scores by balancing sensitivity and specificity..ResultsMDD-W exhibited a positive correlation (ρ = 0.159, 95% CI: 0.065–0.250) (p = 0.001) and demonstrated strong predictive ability (AUC = 0.839, 95% CI: 0.80–0.88; p value = 0.001) for the mean adequacy ratio in assessing micronutrient adequacy. The sensitivity and specificity of the MDD-W at the standard cutoff of ≥5 food groups were found to be 69.9 and 5.3%, respectively. Additionally, the optimal cutoff points for dietary diversity and food variety scores in predicting micronutrient adequacy were determined to be 3.42 and 4.67, respectively. The food variety indicator based on nine food groups showed a negative correlation (ρ = −0.402, 95% CI: −0.137-0.053) (p > 0.05) and remained a poor predictor (AUC = 0.709, 95% CI: 3.49 to 4.03) of the mean adequacy ratio.ConclusionMDD-W was positively correlated with micronutrient intake adequacy and demonstrated good predictive ability. At the standard cutoff of ≥5 food groups, its sensitivity and specificity were 69.9 and 5.3%, respectively. However, the findings differed from those of other studies, and discrepancies with FAO recommendations regarding the cutoff values and performance levels of MDD-W were observed, indicating a need for further investigation.